Mining players’ experience in computer games: Immersion affects flow but not presence - Colombo, Simone; Hansson, Patrik; Nyström, Markus B.T. (Computers in human behavior reports, 2023)
The aim of this study was to investigate whether different levels of immersion while playing a computer game affect the participant's experiences of flow and presence. Understanding how different levels of immersion influence the experiences of flow and presence can shed light on the intricate interplay between these constructs and provide valuable insights into the factors that contribute to engaging and immersive gameplay. The independent variable, immersion, was manipulated in three conditions (high, moderate, and low) in a between-subject design within the video game Minecraft. Participants were asked to complete 15 min of gameplay and then fill out the questionnaires concerning flow and presence. The experiment was conducted remotely on a video-sharing platform. Bayesian analysis revealed an effect of immersion level on flow, while no evidence of an effect was found for the experience of presence. This study provides evidence in favor of a relation between flow and immersion while supporting a presumed double dissociation of immersion from presence. Future research using a Bayesian approach is encouraged to build further knowledge on this research topic. •The analysis shows a significant effect of high levels of gameplay immersion on the experience of flow•The analysis shows no significant effect for different levels of gameplay immersion on the feeling of presence•Flow and presence represent different constructs of the gameplay experience•Bayesian statistics provides stronger evidence in favor of a relation between flow and immersion rather than between presence and immersion